Design and test of a multi-edge toothed cutting device for membrane-impurity mixed material - Liang, Rongqing; Zhang, Bingcheng; Chen, Xuegeng; Meng, Hewei; Wang, Xinzhong; Shen, Congju; Li, Yaping; Kan, Za (International Journal of Agricultural and Biological Engineering, 2023)
As the existing residual film crushing device in Xinjiang cannot directly crush membrane-impurity mixed material, by analyzing the compressive and cutting force characteristics of residual film material layer and cotton stalk, the cutting conditions of mixed materials were obtained, and the method of cutting was determined. A multi-edge toothed cutters was created, and a cutting device was built. It was preliminarily determined that the number of teeth in the cutters was 8, the clearance between the teeth and between the tooth and fixed blade was 3 mm, the speed of the high-speed cutter was 800 r/min, and the speed difference between the high- and low-speed cutters was –300 r/min. Test results show that the ratio of residual film to total residual film sampling mass was (2.22±0.3)%, (19.19±2.02)%, (58.94±3.19)% and (20.65±2.05)%, respectively, when the maximum outer profile size in the range of [0,20) mm, [20,100) mm, [100,500) mm and [500,~) mm. The mass of cotton stalks with lengths of [0,50) mm, [50,100) mm and [100,~) mm accounted for (32.57±1.5)%, (27.77±1.3)% and (39.66±1.75)%, respectively, and the cutting power consumption was (85.41±15.63) kJ. The test results can provide a basis for the subsequent membrane-impurity mixed material cutting technology, as well as some guidance for the separation of it.Keywords: multi-edge toothed cutter; membrane-impurity mixed material; cutting device; cutting conditionsDOI: 10.25165/j.ijabe.20231602.7240Citation: Liang R Q, Zhang B C, Chen X G, Meng H W, Wang X Z, Shen C J, Li Y P, Kan Z. Design and test of a multi-edge cutting device for membrane-impurity mixed material. Int J Agric & Biol Eng, 2023; 16(2): 73-84.